Negative Effects of an Exotic Grass Invasion on Small-Mammal Communities - Freeman, Eric D. (Public Library of Science, 2014)
Exotic invasive species can directly and indirectly influence natural ecological communities. Cheatgrass (Bromus tectorum) is non-native to the western United States and has invaded large areas of the Great Basin. Changes to the structure and composition of plant communities invaded by cheatgrass likely have effects at higher trophic levels. As a keystone guild in North American deserts, granivorous small mammals drive and maintain plant diversity. Our objective was to assess potential effects of invasion by cheatgrass on small-mammal communities. We sampled small-mammal and plant communities at 70 sites (Great Basin, Utah). We assessed abundance and diversity of the small-mammal community, diversity of the plant community, and the percentage of cheatgrass cover and shrub species. Abundance and diversity of the small-mammal community decreased with increasing abundance of cheatgrass. Similarly, cover of cheatgrass remained a significant predictor of small-mammal abundance even after accounting for the loss of the shrub layer and plant diversity, suggesting that there are direct and indirect effects of cheatgrass. The change in the small-mammal communities associated with invasion of cheatgrass likely has effects through higher and lower trophic levels and has the potential to cause major changes in ecosystem structure and function.